2004
DOI: 10.1093/jis/4.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific competition in the speckled wood butterfly Pararge aegeria: Effect of rearing density and gender on larval life history

Abstract: In insects, the outcome of intraspecific competition for food during development depends primarily upon larval density and larval sex, but effects will also depend on the particular trait under consideration and the species under study. Experimental manipulations of larval densities of a Madeiran population of the speckled wood butterfly Pararge aegeria confirmed that intraspecific competition affected growth. As densities increased P. aegeria adults were smaller and larval development periods were longer. Sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 48 publications
1
32
0
2
Order By: Relevance
“…Therefore, if ample food is not supplied during larval stages, it affects the females more which results in reduced fecundity. Food shortages during larval development may therefore result in a reduction in fecundity which was also reported by (Gibbs, et al, 2004).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Therefore, if ample food is not supplied during larval stages, it affects the females more which results in reduced fecundity. Food shortages during larval development may therefore result in a reduction in fecundity which was also reported by (Gibbs, et al, 2004).…”
Section: Discussionmentioning
confidence: 54%
“…Long larval development periods are generally considered to be disadvantageous since they may limit opportunities for reproduction (Fischer et al, 2000). Gibbs et al (2004), working on a population of Par arge aegeria, found that intraspecific competition affected growth and development in the insect with females more adversely affected by high density than males because females are completely dependent on their larval derived resources for reproduction. Intraspecific competition may sometimes be beneficial as reported by Sillanpaa (2009) in Epirrita autumnata, where crowding may trigger increased consumption and faster development to avoid impending food shortage on good quality food.…”
Section: Introductionmentioning
confidence: 99%
“…In female P. aegeria , resources for reproduction are, to a significant degree, obtained during the larval stage and there is little opportunity to obtain more nitrogenous resources for reproduction through adult feeding (Karlsson 1994) or nuptial gifts (Svärd and Wiklund 1989). Nutrient stress during larval growth prolongs development and results in lighter, small‐sized P. aegeria adults at eclosion, and females are more adversely affected than males (Gibbs et al. 2004, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…A genotype is non‐plastic if it shows the same phenotype in all environments (Pigliucci, 2001). Environmental conditions can have deep impacts on the fitness and behavior of the adult insect, as seen when the larval density of a speckled Pararge aegeria L. population (Lepidoptera; Nymphalidae) was manipulated in order to have many individuals and low food availability, resulting in a drastic reduction in the population size, demonstrating the effects of intraspecific competition on the growth and development of this species (Gibbs et al , 2004). The bean weevil Zabrotes subfasciatus Boheman (1883) (Coleoptera; Chrysomelidae; Bruchinae; Amblycerini) can also ensure the survival of its offspring by ovipositing bigger, yet fewer, eggs, amid limited host availability (Teixeira et al , 2009).…”
Section: Introductionmentioning
confidence: 99%